Systematic review of clinical drug development activities for neuroblastoma from 2011 to 2020. Issue 5 (2nd December 2022) - Nader, Jaclynne H.; Bourgeois, Florence; Bagatell, Rochelle; Moreno, Lucas; Pearson, Andrew D. J.; DuBois, Steven G.
Abstract: Background: Understanding the landscape of clinical trials for patients with neuroblastoma may inform efforts to improve drug development. Procedure: We evaluated therapeutic trials for patients with neuroblastoma from 2011 to 2020 in our search using clinical trial information from ClinicalTrials.gov, Clinicaltrialregister.eu, PubMed, and American Society of Clinical Oncology (ASCO) annual meeting collection. Trends in trials and treatments over time were evaluated qualitatively. Results: A total of 192 trials met inclusion criteria. A median of 20.5 trials were started per year, which was stable over time. There were 87 (45%) phase 1, 100 (51%) phase 2, and only five (2.6%) phase 3 trials. The median time to completion was 4.9 years for phase 1 and 2 trials (no phase 3 trials reported as completed during the study period). In all, 34% of trials were international, while 20% of trials were intercontinental. Eighty‐nine percent of nonmyeloablative trials included at least one novel agent. 48% of these trials studied combination therapies, and 86% of these combinations included conventional chemotherapy. Among 157 trials that included a targeted agent, 78 targets were identified, with GD2 being the primary target under investigation in 16.7% of these trials. Only eight trials were included in regulatory decisions, which led to European Medicines Agency (EMA) or Food and Drug Administration (FDA) approval for neuroblastoma. Conclusions: The large number of trials initiated per year, the range of targets, and the rate of intercontinental collaboration are encouraging. The paucity of late‐stage trials, the prolonged trial duration, and relative lack of combination studies are major causes of concern. This work will inform future drug development for neuroblastoma.